Al-Fatihah: Mencari Makna Melalui Tanda (Aplikasi Teori Semiotika Charles Morris) - Maslekhan, M. Fahmi Fahreza Al Muzakki (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2024)
Abstract: Semiotics is the study of "signs", both systematic signs in sentence structures and other than sentences. So far, semiotics has often been used as a linguistic analysis knife, including in analysing the sentence structure of Qur'anic verses. This research aims to explore the meaning of Surah Al-Fatihah using Charles Morris' semiotic theory with qualitative methods and data presentation in the form of descriptive-analysis. The research data is obtained by literature study, collected from primary sources, namely the Qur'an and secondary sources that have relevance to the research. The result of this study informs that Charles Morris' semiotics has a suitability in interpreting the Qur'anic verses, because in Morris' semiotics there are semiotic branch sciences that must be applied, namely; syntax, semantics and pragmatics. Through this knowledge, it was finally found that Surah Al-Fatihah can be categorised into two levels, namely; Rububiyyah which is contained in verses 1-4 and 'Ubudiyyah which is contained in verses 5-7. While the meaning content that can be found includes; tauhid, praise, faith, prayer and history of previous people.